if 2 zeros of polynomial x⁴-6x³-26x²+138x-35 are 2±√3, find other zeros.
Answers
Answered by
110
hi friend,
given 2 zeros are 2±√3
sum of zeros=2+√3+2-√3=4
product of zeros =4-3=1
so the quadratic polynomial from given 2 zeros are x²-4x+1-----(1)
given x⁴-6x³-26x²+138x-35 ----(2)
dividing (2) by (1), we get x²-2x-35
→x²-7x+5x-35
→x(x-7)+5(x-7)
→(x+5)(x-7)
so the other roots are -5 and 7
I hope this will help u ;)
given 2 zeros are 2±√3
sum of zeros=2+√3+2-√3=4
product of zeros =4-3=1
so the quadratic polynomial from given 2 zeros are x²-4x+1-----(1)
given x⁴-6x³-26x²+138x-35 ----(2)
dividing (2) by (1), we get x²-2x-35
→x²-7x+5x-35
→x(x-7)+5(x-7)
→(x+5)(x-7)
so the other roots are -5 and 7
I hope this will help u ;)
Anonymous:
thank you
Answered by
82
Hi there !
Since 2+ √3 is a zero,
x-(2+√3) is a factor of the polynomial.
Since 2-√3 is a zero,
x-(2-√3) is a factor of the polynomial.
This means that (x-2-√3)(x-2+√3) are factors
(x-2-√3)(x-2+√3) [ using identity ]
= (x-2)² - (√3)²
= x² -4x +4 - 3
= x²- 4x+1
x²- 4x+1 is a factor of x⁴-6x³-26x²+138x-35
WE have to perform division algorithm ,
divide x⁴-6x³-26x²+138x-35 with x²- 4x+1
we get the answer as :-
x²- 2x - 35
Now split the middle terms !!
x²- 7x + 5x - 35
x [ x - 7 ] + 5 [ x - 7 ]
[ x+ 5 ] [ x - 7 ]
The other zeroes are :-
-5 and 7
..
Since 2+ √3 is a zero,
x-(2+√3) is a factor of the polynomial.
Since 2-√3 is a zero,
x-(2-√3) is a factor of the polynomial.
This means that (x-2-√3)(x-2+√3) are factors
(x-2-√3)(x-2+√3) [ using identity ]
= (x-2)² - (√3)²
= x² -4x +4 - 3
= x²- 4x+1
x²- 4x+1 is a factor of x⁴-6x³-26x²+138x-35
WE have to perform division algorithm ,
divide x⁴-6x³-26x²+138x-35 with x²- 4x+1
we get the answer as :-
x²- 2x - 35
Now split the middle terms !!
x²- 7x + 5x - 35
x [ x - 7 ] + 5 [ x - 7 ]
[ x+ 5 ] [ x - 7 ]
The other zeroes are :-
-5 and 7
..
Similar questions